TSG-6 modulates the interaction between hyaluronan and cell surface CD44. - Lesley, J; Gál, I; Mahoney, D; Cordell, MR; Rugg, MS; Hyman, R; Day, A; Mikecz, K (2004)
Interactions between CD44 and hyaluronan are implicated in the primary adhesion of lymphocytes to endothelium at inflammatory locations. Here we show that preincubation of hyaluronan with full-length recombinant TSG-6 or its Link module domain (Link_TSG6) enhances or induces the binding of hyaluronan to cell surface CD44 on constitutive and inducible cell backgrounds, respectively. These effects are blocked by CD44-specific antibodies and are absent in CD44-negative cells. Enhancement of CD44-mediated interactions of lymphoid cells with hyaluronan by TSG-6 proteins was seen under conditions of flow at shear forces that occur in post-capillary venules. Increases in the number of rolling cells were observed on substrates comprising TSG-6-hyaluronan complexes as compared with a substrate containing hyaluronan alone. In ligand competition experiments, cell surface-bound TSG-6-hyaluronan complexes were more potent than hyaluronan alone in inhibiting cell adhesion to immobilized hyaluronan. Link_TSG6 mutants with impaired hyaluronan binding function had a reduced ability to modulate ligand binding by cell surface CD44. However, some mutants that exhibited close to wild-type hyaluronan binding were found to have either reduced or increased activity, suggesting that some amino acid residues outside of the hyaluronan binding site might be involved in protein self-association, potentially leading to the formation of cross-linked hyaluronan fibers. In turn, cross-linked hyaluronan could increase the binding avidity of CD44 by inducing receptor clustering. The ability of TSG-6 to modulate the interaction of hyaluronan with CD44 has important implications for CD44-mediated cell activity at sites of inflammation, where TSG-6 is expressed.